An electrically conductive pressure-sensitive adhesive composition, a pressure-sensitive adhesive tape and a preparation method thereof
By preparing an energized adhesive composition containing PEDOT/PSS, nano core-shell materials and dynamic crosslinking agent, the problem of insufficient conductivity and environmental stability of existing adhesives in flexible electronic devices is solved, and an adhesive with high conductivity, dynamic responsiveness and interface compatibility is achieved, which is suitable for electrical response assembly scenarios.
Patent Information
- Application Number
- CN202510483889.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-17
- Publication Date
- 2025-07-08
- Estimated Expiration
- 2045-04-17
AI Technical Summary
It is difficult for existing adhesives to achieve high conductivity, dynamic responsiveness, environmental stability and interface compatibility at the same time in flexible electronic devices, resulting in the device's adhesion failure under extreme conditions, limiting its application in special fields.
The energized adhesive composition consisting of polyurethane acrylate, PEDOT/PSS solution, nanocore and shell materials, dynamic crosslinking agents, TPU particles, etc. is used to achieve electric field-controlled adhesion through the electron-ion dual-path conductivity and dynamic crosslinking network of PEDOT/PSS, combining the mechanical strength and flexibility of nanocore and shell materials and TPU particles.
It realizes significant differences in adhesion of adhesives in power-on and non-energized states, high temperature stability and cycle stability, excellent anti-pollution performance, and is suitable for lossless disassembly and reuse in electrical response assembly scenarios.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive materials, in particular to an electrically conductive viscosity-reducing adhesive composition, a viscosity-reducing adhesive tape and a preparation method thereof. Background Art
[0002] With the rapid development of flexible electronics, smart sensors and wearable devices, the demand for functional adhesive materials is growing. Traditional adhesives have significant limitations in conductivity, dynamic responsiveness and environmental adaptability, and it is difficult to meet the complex requirements of emerging application scenarios for material performance. For example, in flexible electronic devices, adhesive materials must have high conductivity to transmit signals, adjustable adhesion to adapt to dynamic deformation, and long-term stability to cope with complex environments. However, most conductive adhesives in the prior art rely on a single conductive filler, and their mechanical properties and conductivity are often difficult to balance, and they lack the ability to respond intelligently to external stimuli. In addition, under extreme conditions such as high temperature and high humidity, the interface of traditional materials is prone to oxidation or degradation, resulting in destruction of the conductive network or adhesion failure, which seriously restricts the reliability and service life of the device.
[0003] Although current research attempts to improve material properties by introducing dynamic cross-linking or nanocomposite structures, it still faces many challenges. On the one hand, dynamic cross-linking systems are often difficult to achieve rapid and reversible adhesion regulation due to their slow response speed and poor cyclic stability; on the other hand, the interface compatibility problem between nanofillers and the matrix can easily cause agglomeration or stress concentration, weakening the overall performance of the material. In addition, the shortcomings of existing conductive adhesives in anti-pollution and anti-aging properties further limit their application in special fields such as biomedicine and marine engineering. Therefore, the development of an intelligent adhesive that combines high conductivity, dynamic responsiveness, environmental stability and interface compatibility has become a key direction to break through the technical bottleneck of the industry. Summary of the invention
[0004] The object of the present invention is to provide an electrically conductive viscosity-reducing adhesive composition, a viscosity-reducing adhesive tape and a preparation method thereof, so as to solve the problems raised in the background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] An electrical viscosity-reducing adhesive composition is prepared by using the following raw materials counted in parts by weight:
[0007] Polyurethane acrylate 60-70 parts;
[0008] 10-14 parts of PEDOT / PSS solution;
[0009] 4-8 parts of nano core-shell material;
[0010] 8-12 parts of dynamic cross-linking agent;
[0011] 2.5 - 3.5 parts of TPU particles;
[0012] 1 - 2 parts of hydrogenated rosin tackifying resin;
[0013] 0.4 - 0.6 parts of polybutylene adipate;
[0014] 0.2 - 0.4 parts of antioxidant;
[0015] 0.1 - 0.2 parts of zwitterion - polyethylene glycol copolymer;
[0016] Furthermore, the solvent of the PEDOT / PSS solution is dimethyl sulfoxide; the mass fraction of PEDOT / PSS in the solution is 1.2 - 1.5%.
[0017] It should be noted that PSS (polystyrene sulfonate) acts as a dopant and dispersant to help the PEDOT (poly(3,4 - ethylenedioxythiophene)) conductive polymer disperse and dissolve in the solvent. The conjugated main chain of PEDOT allows electrons to be transported along the chain. The sulfonic acid group of PSS ionizes into H + and - SO3 - , providing an ion migration channel. The oxidized state of PEDOT (PEDOT + ) forms a charge transfer complex with PSS - to achieve electron - ion dual - path conduction. When powered on, the orientation of the PEDOT chain changes, the surface energy decreases (the contact angle increases), resulting in a decrease in adhesion force. At the same time, it forms a continuous conduction path synergistically with the silver nanowires in the nanocore - shell material, reducing the interface resistance. Dimethyl sulfoxide (DMSO) acts as both a solvent and a secondary dopant. By weakening the Coulomb repulsion between the PEDOT and PSS chains, it significantly improves the conductivity of PEDOT / PSS, induces the rearrangement of the PEDOT chain, enhances the π - π stacking, and can better fill the gaps between the silver nanowires, reducing interface defects. The PEDOT / PSS solution with DMSO as the solvent not only improves the hole - transport efficiency but also reduces the electron - transport impedance by optimizing the interface contact, forming an efficient dual - path structure. In addition, the pH of PEDOT / PSS is acidic, and PEDOT / PSS may aggregate under acidic or alkaline conditions. The DMSO solvent can maintain the pH of the system at neutral to ensure dispersion stability.
[0018] Furthermore, the preparation steps of the nanocore - shell material are as follows:
[0019] A1. Disperse silver nanowires in a PVP / ethanol solution for pretreatment, perform ultrasonic treatment for 30 min, centrifuge, disperse the pretreated silver nanowires in an ethanol / water mixed solution, add 0.1 mol / L tetraethyl orthosilicate solution and 0.5 mol / L ammonia water, stir at room temperature for 12 h, centrifuge at a speed of 12000 r / min for 10 min, and wash with ethanol three times to obtain a core-shell material;
[0020] Further, the mass fraction of PVP in the PVP / ethanol solution is 1%;
[0021] Further, the volume ratio of ethanol to water in the ethanol / water mixed solution is 4:1;
[0022] Further, the solvent of the tetraethyl orthosilicate solution is an ethanol / water mixed solution;
[0023] Further, the dosage ratio of the silver nanowires to the PVP / ethanol solution is 1 g:(90 - 110) mL;
[0024] Further, the dosage ratio of the pretreated silver nanowires, ethanol / water mixed solution, tetraethyl orthosilicate solution and ammonia water is 1 g:(180 - 220) mL:20 mL:10 mL;
[0025] A2. Disperse the core-shell material in an acetic acid buffer solution with a pH of 5.5, perform ultrasonic treatment for 30 min, perform 50 W oxygen plasma treatment for 5 min, centrifuge, wash, and dry to obtain an AgNWs@SiO2 material;
[0026] Further, the dosage ratio of the core-shell material to the acetic acid buffer solution is 1 g:50 mL;
[0027] A3. Add 3-mercaptopropyltrimethoxysilane to an ethanol aqueous solution, adjust the pH value to 8 - 9 with 0.1 mol / L NaOH solution, stir and dissolve to obtain a 3-mercaptopropyltrimethoxysilane hydrolysis solution; disperse the AgNWs@SiO2 material in the 3-mercaptopropyltrimethoxysilane hydrolysis solution, stir at 60 °C for 6 h under a nitrogen atmosphere, centrifuge, wash, and dry to obtain a nano core-shell material;
[0028] Further, the dosage ratio of the AgNWs@SiO2 material to the 3-mercaptopropyltrimethoxysilane hydrolysis solution is 1 g:(90 - 110) mL.
[0029] Further, the volume ratio of 3-mercaptopropyltrimethoxysilane, absolute ethanol and deionized water in the 3-mercaptopropyltrimethoxysilane hydrolysis solution is 1:(25 - 50):(5 - 10).
[0030] It should be noted that the surface of silver nanowires is pretreated with a PVP / ethanol solution to prevent aggregation during the SiO2 deposition process. By controlling the hydrolysis rate of TEOS, a uniform SiO2 shell layer is formed on the surface of silver nanowires. Acid treatment and plasma treatment enhance the activation of the hydroxyl density on the SiO2 surface, and MPTS surface treatment is used to introduce mercapto groups to obtain the AgNWs@SiO2-SH nanocore-shell material. In the nanocore-shell material, silver nanowires form an electron transport backbone, and PEDOT fills the gaps between silver nanowires to form an electron-hole dual pathway and construct a conductive network. The SiO2 shell layer can isolate oxygen / moisture to prevent the oxidation of silver nanowires. The nanocore-shell material with high conductivity can promote the uniform distribution of the electric field by reducing the resistance gradient. The uniform electric field can destroy the dynamic cross-linking bonds through interfacial polarization or redox reactions, triggering the rapid dissociation of the dynamic cross-linking agent. The introduced mercapto groups react with the residual isocyanate groups in PUA to generate thiocarbamate bonds, enhancing the cross-linking density of PUA. Its dynamic reversibility promotes a more ordered cross-linking structure, reduces phonon scattering, and improves the thermal conduction efficiency. The nanocore-shell material can improve the mechanical strength and thermal stability of the electro-conductive tackifying adhesive composition. In addition, the dynamic reversibility of the thiocarbamate bond is also reflected in that when an electric current is applied, Joule heat is generated due to the resistance inside the colloid, and the local temperature rises to the breaking threshold of the thiocarbamate bond, which can lead to bond breakage and interfacial debonding. The C-S bond of the thiocarbamate bond is more resistant to hydrolysis than the C-O bond, which can improve the moisture and heat aging resistance of the composition to a certain extent.
[0031] Furthermore, the dynamic cross-linking agent is ferrocene and β-cyclodextrin with a molar ratio of 1:(1 - 1.2).
[0032] It should be noted that ferrocene (Fc) and β-cyclodextrin (β-CD) form a dynamic cross-linking network through host-guest inclusion. In the neutral state, the hydrophobic ferrocene group of Fc highly matches the hydrophobic cavity of β-CD to form a stable inclusion complex. When a voltage is applied: Oxidation triggers dissociation: Fc is oxidized to positively charged ferrocenium ion (Fc + ), whose volume increases (due to the change in the ionic radius of the oxidized state Fe 3+ ) and its polarity increases, resulting in a decrease in the matching degree with the β-CD cavity and the disruption of the host-guest interaction, and the cross-linking network dissociates. Reduction restores cross-linking: When the voltage is removed or a reverse voltage is applied, Fc + is reduced to neutral Fc and rebinds with β-CD to achieve the reversible reorganization of the cross-linking network. As mentioned above, the AgNWs@SiO2-SH nanocore-shell material can promote the uniform distribution of the electric field, thus ensuring the synchronous dissociation of the Fc / β-CD dynamic cross-linking network when an electric current is applied. The dielectric shielding effect of the SiO2 shell layer can regulate the local electric field gradient to avoid irreversible damage to the colloid caused by local overload.
[0033] It should be noted again that voltage triggers the oxidation and crosslinking dissociation of Fc, destroying the network cohesion and reducing the colloidal adhesion force; after removing the voltage, Fc + is reduced and recombines with β-CD, restoring the colloidal adhesion force. At the same time, the thiocarbamate bond breaks synchronously with the assistance of Joule heat on the one hand, accelerating the debonding response, and on the other hand, synergistically enhancing the adhesion force when not powered on; the multiple hydrogen bonds of β-CD and the dynamic crosslinking of Fc / β-CD form a hierarchical network, dispersing stress and suppressing long-term deformation, improving the anti-creep performance; the hydrophobic cavity of β-CD reduces water penetration, improving the moisture and heat resistance of the composition. In addition, the dynamic crosslinking agent can also increase the storage modulus and toughness of PUA.
[0034] Furthermore, the hardness of the TPU particles is 60A - 70A.
[0035] It should be noted that the hard segments of TPU (such as MDI / BDO) form physical crosslinking points through hydrogen bonds or microcrystals, and the soft segments (such as polyester / polyether) provide elasticity, forming a microphase separation structure. The hard segment microdomains have a stable storage modulus at a high temperature of 100 °C, which can inhibit the slippage of polymer chains and reduce the creep rate; the TPU soft segments dissipate impact energy through molecular chain slippage and conformational changes, increasing the elongation at break. In addition, the high specific surface area of the TPU particles enhances the physical entanglement and hydrogen bond interaction with the PUA matrix, reducing stress concentration; the elastic matrix of the TPU particles disperses external bending / tensile stress, preventing the fracture of the silver nanowire network; the urethane groups of TPU form hydrogen bonds with the sulfonic acid groups of PSS, reducing phase separation; the thermal decomposition temperature of TPU is greater than 200 °C, and its heat resistance and the SiO2 shell synergistically delay the high-temperature oxidation and structural collapse of AgNWs.
[0036] It should be noted that poly(butylene adipate) replaces traditional phthalates as a plasticizer, increasing the heat distortion temperature and having good compatibility, which can reduce the precipitation of plasticizer and phase separation migration inside the composition.
[0037] Furthermore, the antioxidant is one or more of dibutylhydroxytoluene (BHT) and benzotriazole (BTA).
[0038] It should be noted that low-potential antioxidants are selected as antioxidants to avoid interfering with the oxidation of Fc, inhibiting the side reactions of Fc oxidation by scavenging free radicals. At the same time, the weak reducibility of the -SH group helps to maintain the steady state of Fc and prolong the dynamic crosslinking cycle life.
[0039] Furthermore, the zwitterionic - polyethylene glycol copolymer is one or two of sulfobetaine - polyethylene glycol copolymer, carboxybetaine - polyethylene glycol copolymer, phosphatidylcholine - polyethylene glycol copolymer, phosphobetaine - polyethylene glycol copolymer and aminobetaine - polyethylene glycol copolymer, and the molecular weight range of the polyethylene glycol chain segment is 2000 - 5000 Da.
[0040] It should be noted that the zwitterionic - polyethylene glycol copolymer is composed of a zwitterion with a neutral charge and a hydrophilic polyether chain segment (polyethylene glycol PEG) that provides steric hindrance. The zwitterionic structure adsorbs water molecules to form a dense hydration layer, physically blocking proteins and pollutants from approaching the surface and providing charge shielding, and the surface neutrality reduces electrostatic adsorption, endowing the composition with anti - fouling properties; the flexible PEG chain segment fills the interfacial microcracks, reducing the interfacial peeling caused by the dissociation of dynamic cross - linking, and the hydration layer reduces the attack of free radicals (such as ·OH) on the dynamic cross - linker (Fc / β - CD), inhibiting the irreversible side reaction of Fc + to improve the cycle stability.
[0041] Furthermore, for scenarios that require higher anti - fouling properties and moderate flexibility, a zwitterionic - polyethylene glycol copolymer with a PEG molecular weight of 2000 - 3000 Da is selected; for scenarios that require higher heat resistance, a zwitterionic - polyethylene glycol copolymer with a PEG molecular weight of 4000 - 5000 Da is selected; for better comprehensive performance, a zwitterionic - polyethylene glycol copolymer with a PEG molecular weight of 3000 - 4000 Da is selected.
[0042] It should be noted that if the PEG chain segment is short, the steric hindrance is insufficient, which may lead to the aggregation of the nanoparticle nanocore - shell material or a decrease in the anti - fouling property, and the hydrophilicity is weak, resulting in a limited hydration layer thickness; if the PEG chain segment is too long, it may hinder the movement of the dynamic cross - linker, affecting the electric field response speed, and the high flexibility may lead to a decrease in the mechanical strength (storage modulus) of the material.
[0043] A preparation method of an electro - conductive viscosity - reducing adhesive composition includes the following steps:
[0044] S1. At 25 - 30 °C, add 60 - 70 parts of polyurethane acrylate and 0.4 - 0.6 parts of polybutylene adipate into a planetary stirring kettle, and stir at a speed of 200 - 300 r / min for 10 - 12 min;
[0045] S2. Gradually add 10 - 14 parts of PEDOT / PSS solution, and stir at a speed of 500 - 600 r / min for 15 - 20 min;
[0046] S3. Transfer the mixed material obtained in S2 to an ultrasonic disperser, slowly add 4 - 8 parts of nano core - shell material, with a frequency of 20 kHz and a power of 300 W, and ultrasonically disperse for 15 min while maintaining a temperature below 30 °C;
[0047] S4. Transfer the mixed material obtained in S3 back to the planetary stirring kettle, sequentially add 8 - 12 parts of dynamic cross - linker and 1 - 2 parts of hydrogenated rosin tackifying resin, and stir at a speed of 300 - 400 r / min for 18 - 20 min;
[0048] S5. Add 2.5 - 3.5 parts of TPU particles, and stir at a speed of 400 - 600 r / min for 20 - 25 min;
[0049] S6. Add 0.2 - 0.4 parts of antioxidant and 0.1 - 0.2 parts of zwitterion - polyethylene glycol copolymer, and stir at a speed of 150 - 200 r / min for 10 - 12 min to obtain a mixed adhesive;
[0050] S7. Vacuum - degas the mixed adhesive liquid for 20 min to prepare an electrically conductive tack - reducing adhesive composition.
[0051] An electrically conductive tack - reducing tape comprises a release film layer I, an adhesive layer, and a release film layer II, and the adhesive layer is obtained by curing the electrically conductive tack - reducing adhesive composition.
[0052] A preparation method of an electrically conductive tack - reducing tape is as follows:
[0053] Uniformly coat the electrically conductive tack - reducing adhesive composition on the release film layer I using a doctor blade coater, and perform UV curing for 60 - 90 s to obtain an adhesive layer, and then laminate the release film layer II on the other side of the adhesive layer to prepare the electrically conductive tack - reducing tape.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] The electrically conductive tack - reducing adhesive composition and the tack - reducing tape prepared by the present invention have excellent mechanical properties, sensitive response, significant difference in peel strength before and after electrification, high - temperature stability, cycle stability, and anti - pollution. By virtue of the characteristic of regulating adhesion force through an electric field, the non - destructive disassembly and reuse of devices can be realized, and it has broad application prospects in the field of electro - responsive assembly. Specific Embodiments
[0056] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Apparently, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0057] The sources and parameters of some materials are shown in Table 1.
[0058] (1) The preparation steps of the PEDOT / PSS solution are as follows:
[0059] Dissolve 1.68 g of PEDOT:PSS powder in 100 mL of dimethyl sulfoxide and homogenize to obtain a PEDOT / PSS solution with a mass fraction of PEDOT:PSS of 1.5%.
[0060] (2) The preparation steps of the nano core-shell material are as follows:
[0061] A1. Disperse 1 g of silver nanowires in 100 mL of a PVP / ethanol solution with a PVP mass fraction of 1% for pretreatment, ultrasonically treat for 30 min, centrifuge, disperse 1 g of the pretreated silver nanowires in 200 mL of an ethanol / water mixed solution with a volume ratio of ethanol to water of 4:1, add 20 mL of a tetraethyl orthosilicate solution with a concentration of 0.1 mol / L (the solvent is an ethanol / water mixed solution with a volume ratio of ethanol to water of 4:1) and 10 mL of a 0.5 mol / L ammonia water, stir at room temperature for 12 h, centrifuge at a speed of 12000 r / min for 10 min, and wash with ethanol 3 times to obtain the core-shell material;
[0062] A2. Disperse 1 g of the core-shell material in 50 mL of an acetic acid buffer solution with a pH of 5.5, ultrasonically treat for 30 min, treat with 50 W of oxygen plasma for 5 min, centrifuge, wash until neutral, and dry to obtain the AgNWs@SiO2 material;
[0063] A3. Add 10 mL of 3-mercaptopropyltrimethoxysilane to 100 mL of an ethanol aqueous solution with a volume ratio of ethanol to water of 9:1, adjust the pH value to 8.5, stir and dissolve to obtain a 3-mercaptopropyltrimethoxysilane hydrolysis solution; disperse 1 g of the AgNWs@SiO2 material in 100 mL of the 3-mercaptopropyltrimethoxysilane hydrolysis solution, stir at 60 °C for 6 h under a nitrogen atmosphere, centrifuge, wash, and dry to obtain the nano core-shell material.
[0064] (3) The preparation steps of the dynamic cross-linking agent are as follows:
[0065] Add 93 g of Fc and 624 g of β-CD to 1000 mL of a mixed solution with a volume ratio of ethanol to deionized water of 1:19, stir at 60 °C for 2 h until completely dissolved, stand at room temperature for 12 h, centrifuge, freeze, and dry to obtain the dynamic cross-linking agent.
[0066] Example 1:
[0067] The preparation method of an electroconductive viscosity-reducing adhesive composition is as follows:
[0068] S1. Add 65 parts of polyurethane acrylate and 0.5 part of polybutylene adipate to a planetary stirring kettle at 25°C, and stir for 10 min at a speed of 200 r / min;
[0069] S2. Gradually add 12 parts of PEDOT / PSS solution, and stir for 15 min at a speed of 500 r / min;
[0070] S3. Transfer the mixed material obtained in S2 to an ultrasonic disperser, slowly add 6 parts of nano core-shell material, 20 kHz, power 300 W, ultrasonically disperse for 15 min, and maintain below 30°C;
[0071] S4. Transfer the mixed material obtained in S3 back to the planetary stirring kettle, sequentially add 10 parts of dynamic crosslinking agent and 1.5 parts of hydrogenated rosin tackifying resin, and stir for 20 min at a speed of 300 r / min;
[0072] S5. Add 3 parts of TPU particles, and stir for 25 min at a speed of 500 r / min;
[0073] S6. Add 0.3 part of dibutylhydroxytoluene and 0.15 part of carboxybetaine-polyethylene glycol copolymer, and stir for 10 min at a speed of 150 r / min to obtain a mixed glue;
[0074] S7. Vacuum degas the mixed glue solution for 20 min to obtain an electrified viscosity-reducing glue composition.
[0075] A method for preparing an electrified viscosity-reducing tape is as follows:
[0076] Use a doctor blade coater to evenly coat the electrified viscosity-reducing glue composition on the release film layer I, and cure it by UV for 80 s to obtain an adhesive layer, and attach the release film layer II to the other side of the adhesive layer to obtain an electrified viscosity-reducing tape.
[0077] Example 2:
[0078] A method for preparing an electrified viscosity-reducing glue composition is as follows:
[0079] S1. Add 60 parts of polyurethane acrylate and 0.4 part of polybutylene adipate to a planetary stirring kettle at 25°C, and stir for 10 min at a speed of 200 r / min;
[0080] S2. Gradually add 10 parts of PEDOT / PSS solution, and stir for 15 min at a speed of 500 r / min;
[0081] S3. Transfer the mixed material obtained in S2 to an ultrasonic disperser, slowly add 5 parts of nano core-shell material, 20 kHz, power 300 W, ultrasonically disperse for 15 min, and maintain below 30°C;
[0082] S4. Transfer the mixed material obtained in S3 back to the planetary stirring kettle, sequentially add 8 parts of dynamic cross-linking agent and 1 part of hydrogenated rosin tackifying resin, and stir at a speed of 300 r / min for 20 min;
[0083] S5. Add 2.5 parts of TPU particles and stir at a speed of 500 r / min for 25 min;
[0084] S6. Add 0.2 part of dibutylhydroxytoluene and 0.1 part of carboxybetaine-polyethylene glycol copolymer, and stir at a speed of 150 r / min for 10 min to obtain a mixed glue;
[0085] S7. Vacuum degas the mixed glue solution for 20 min to prepare an electrically conductive tack-reducing glue composition.
[0086] A preparation method of an electrically conductive tack-reducing tape is as follows:
[0087] Use a doctor blade coater to uniformly coat the electrically conductive tack-reducing glue composition on the release film layer I, and perform UV curing for 80 s to obtain an adhesive layer, and laminate the release film layer II on the other side of the adhesive layer to prepare an electrically conductive tack-reducing tape.
[0088] Example 3:
[0089] A preparation method of an electrically conductive tack-reducing glue composition is as follows:
[0090] S1. At 25 °C, add 70 parts of polyurethane acrylate and 0.6 part of polybutylene adipate to the planetary stirring kettle, and stir at a speed of 200 r / min for 10 min;
[0091] S2. Gradually add 14 parts of PEDOT / PSS solution and stir at a speed of 500 r / min for 15 min;
[0092] S3. Transfer the mixed material obtained in S2 to an ultrasonic disperser, slowly add 7 parts of nano core-shell material, 20 kHz, power 300 W, perform ultrasonic dispersion for 15 min, and maintain the temperature below 30 °C;
[0093] S4. Transfer the mixed material obtained in S3 back to the planetary stirring kettle, sequentially add 12 parts of dynamic cross-linking agent and 2 parts of hydrogenated rosin tackifying resin, and stir at a speed of 300 r / min for 20 min;
[0094] S5. Add 3.5 parts of TPU particles and stir at a speed of 500 r / min for 25 min;
[0095] S6. Add 0.4 part of dibutylhydroxytoluene and 0.2 part of carboxybetaine-polyethylene glycol copolymer, and stir at a speed of 150 r / min for 10 min to obtain a mixed glue;
[0096] S7. Vacuum degas the mixed adhesive solution for 20 min to obtain the electroconductive adhesion-reducing adhesive composition.
[0097] A preparation method of an electroconductive adhesion-reducing tape is as follows:
[0098] Use a doctor blade coater to evenly coat the electroconductive adhesion-reducing adhesive composition on the release film layer I, and perform UV curing for 80 s to obtain the adhesive layer. Then, laminate the release film layer II on the other side of the adhesive layer to obtain the electroconductive adhesion-reducing tape.
[0099] Comparative Example 1:
[0100] A preparation method of an electroconductive adhesion-reducing adhesive composition is as follows:
[0101] S1. At 25 °C, add 65 parts of polyurethane acrylate and 0.5 part of polybutylene adipate to a planetary stirring kettle, and stir at a speed of 200 r / min for 10 min;
[0102] S2. Transfer the mixed material obtained in S1 to an ultrasonic disperser, slowly add 6 parts of the nano core-shell material, 20 kHz, power 300 W, and perform ultrasonic dispersion for 15 min while maintaining the temperature below 30 °C;
[0103] S3. Transfer the mixed material obtained in S2 back to the planetary stirring kettle, sequentially add 10 parts of the dynamic crosslinking agent and 1.5 parts of the hydrogenated rosin tackifying resin, and stir at a speed of 300 r / min for 20 min;
[0104] S4. Add 3 parts of TPU particles and stir at a speed of 500 r / min for 25 min;
[0105] S5. Add 0.3 part of dibutylhydroxytoluene and 0.15 part of the carboxybetaine-polyethylene glycol copolymer, and stir at a speed of 150 r / min for 10 min to obtain the mixed adhesive;
[0106] S6. Vacuum degas the mixed adhesive solution for 20 min to obtain the electroconductive adhesion-reducing adhesive composition.
[0107] A preparation method of an electroconductive adhesion-reducing tape is as follows:
[0108] Use a doctor blade coater to evenly coat the electroconductive adhesion-reducing adhesive composition on the release film layer I, and perform UV curing for 80 s to obtain the adhesive layer. Then, laminate the release film layer II on the other side of the adhesive layer to obtain the electroconductive adhesion-reducing tape.
[0109] The difference between this comparative example and Example 1 is that the PEDOT / PSS solution is not added.
[0110] Comparative Example 2:
[0111] A preparation method of an electroconductive adhesion-reducing adhesive composition is as follows:
[0112] S1. At 25 °C, add 65 parts of polyurethane acrylate and 0.5 part of polybutylene adipate to a planetary stirring kettle, and stir at a speed of 200 r / min for 10 min;
[0113] S2. Gradually add 12 parts of PEDOT / PSS solution, and stir at a speed of 500 r / min for 15 min;
[0114] S3. Sequentially add 10 parts of a dynamic crosslinking agent and 1.5 parts of hydrogenated rosin tackifying resin, and stir at a speed of 300 r / min for 20 min;
[0115] S4. Add 3 parts of TPU particles, and stir at a speed of 500 r / min for 25 min;
[0116] S5. Add 0.3 part of dibutylhydroxytoluene and 0.15 part of carboxybetaine-polyethylene glycol copolymer, and stir at a speed of 150 r / min for 10 min to obtain a mixed glue;
[0117] S6. Vacuum degas the mixed glue solution for 20 min to prepare an electrically conductive viscosity-reducing glue composition.
[0118] A preparation method of an electrically conductive viscosity-reducing tape is as follows:
[0119] Apply the electrically conductive viscosity-reducing glue composition evenly on the release film layer I using a doctor blade coater, and perform UV curing for 80 s to obtain an adhesive layer. Bond the release film layer II to the other side of the adhesive layer to prepare an electrically conductive viscosity-reducing tape.
[0120] The difference between this comparative example and Example 1 is that no nanocore-shell material is added.
[0121] Comparative Example 3:
[0122] A preparation method of an electrically conductive viscosity-reducing glue composition is as follows:
[0123] S1. At 25 °C, add 65 parts of polyurethane acrylate and 0.5 part of polybutylene adipate to a planetary stirring kettle, and stir at a speed of 200 r / min for 10 min;
[0124] S2. Gradually add 12 parts of PEDOT / PSS solution, and stir at a speed of 500 r / min for 15 min;
[0125] S3. Transfer the mixed material obtained in S2 to an ultrasonic disperser, slowly add 6 parts of nanocore-shell material, 20 kHz, power 300 W, perform ultrasonic dispersion for 15 min, and maintain the temperature below 30 °C;
[0126] S4. Transfer the mixed material obtained in S3 back to the planetary stirring kettle, add 1.5 parts of hydrogenated rosin tackifying resin, and stir at a speed of 300 r / min for 20 min;
[0127] S5. Add 3 parts of TPU particles and stir at a speed of 500 r / min for 25 min;
[0128] S6. Add 0.3 part of dibutylhydroxytoluene and 0.15 part of carboxybetaine-polyethylene glycol copolymer, and stir at a speed of 150 r / min for 10 min to obtain a mixed glue;
[0129] S7. Vacuum degas the mixed glue solution for 20 min to prepare an electroconductive tackifying glue composition.
[0130] A preparation method of an electroconductive tackifying tape is as follows:
[0131] Use a doctor blade coater to uniformly coat the electroconductive tackifying glue composition on the release film layer I, and cure it by UV for 80 s to obtain an adhesive layer. Bond the release film layer II to the other side of the adhesive layer to prepare an electroconductive tackifying tape.
[0132] The difference between this comparative example and Example 1 is that no dynamic crosslinking agent is added.
[0133] Comparative Example 4:
[0134] A preparation method of an electroconductive tackifying glue composition is as follows:
[0135] S1. At 25 °C, add 65 parts of polyurethane acrylate and 0.5 part of polybutylene adipate to a planetary stirring kettle, and stir at a speed of 200 r / min for 10 min;
[0136] S2. Gradually add 12 parts of PEDOT / PSS solution, and stir at a speed of 500 r / min for 15 min;
[0137] S3. Transfer the mixed material prepared in S2 to an ultrasonic disperser, slowly add 6 parts of nano core-shell material, 20 kHz, power 300 W, ultrasonically disperse for 15 min, and maintain below 30 °C;
[0138] S4. Transfer the mixed material prepared in S3 back to the planetary stirring kettle, sequentially add 10 parts of dynamic crosslinking agent and 1.5 parts of hydrogenated rosin tackifying resin, and stir at a speed of 300 r / min for 20 min;
[0139] S5. Add 3 parts of TPU particles and stir at a speed of 500 r / min for 25 min;
[0140] S6. Add 0.3 part of dibutylhydroxytoluene and stir at a speed of 150 r / min for 10 min to obtain a mixed glue;
[0141] S7. Vacuum degas the mixed glue solution for 20 min to prepare an electroconductive tackifying glue composition.
[0142] The preparation method of the electroconductive anti-adhesive tape is as follows:
[0143] The electroconductive anti-adhesive composition is uniformly coated on the release film layer I by a doctor blade coater and UV-cured for 80 s to obtain an adhesive layer, and the release film layer II is laminated on the other side of the adhesive layer to prepare the electroconductive anti-adhesive tape.
[0144] The difference between this comparative example and Example 1 is that the carboxybetaine-polyethylene glycol copolymer is not added.
[0145] Test:
[0146] I. Shear strength test
[0147] According to "GB / T 7124-2008 Determination of Tensile Shear Strength of Adhesives", the electroconductive anti-adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-4 are torn off one side of the release film and laminated on the aluminum plate substrate, and the other side of the release film is torn off and laminated on another aluminum sheet. The lamination area is 12.5×25 mm, and the shear force is tested after standing for 20 min.
[0148] The test results are shown in Table 2.
[0149] II. 180° peel strength and its reversibility test
[0150] According to "GB / T 2792-2014 Test Method for Peel Strength of Adhesive Tape", the electroconductive anti-adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-4 are tested before energization: after tearing off one side of the release film of the prepared tape, it is laminated on the steel plate, rolled 3 times back and forth with a 2 kg rubber roller, and tested after standing at 23°C for 24 h, and recorded as the peel strength F1 before energization. The electroconductive anti-adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-4 are tested for the peel strength after energization: after tearing off one side of the release film of the tape, it is laminated on the steel plate, rolled 3 times back and forth with a 2 kg rubber roller, and stood at 23°C for 24 h. The laminated sample is energized at 10 V×30 s, and then the 180° peel strength is tested and recorded as the peel strength F after energization. The sample is reattached to a new steel plate, rolled 3 times back and forth with a 2 kg rubber roller, and tested for the re-lamination peel strength after standing at 23°C for 24 h and recorded as the re-lamination peel strength F2 after energization. The recovery ratio calculation formula is as follows:
[0151] Recovery ratio = (F2 / F1)×100%;
[0152] F1—Peel strength before energization;
[0153] F2—Re-lamination peel strength after energization;
[0154] The test results are shown in Table 2.
[0155] III. Heat resistance performance
[0156] According to the "Test Method for Adhesive Retention of Adhesive Tape (GB / T 4851-2014)", a high-temperature retention tester was used. One side of the release film of the current-conducting adhesive-reducing tapes prepared in Examples 1-3 and Comparative Examples 1-4 was torn off and adhered to a stainless steel plate. After being rolled back and forth 2 times with a 2 kg pressure roller and left for 20 min, it was vertically hung, and a 1 kg weight was suspended at the lower end. The dropping time of the test samples at 180 °C was measured respectively, and the residual glue situation was observed. The dropping time of the test samples was used to characterize the adhesion retention ability of the current-conducting adhesive-reducing tape at high temperature.
[0157] The test results are shown in Table 2.
[0158] IV. Surface Resistance Test
[0159] According to the "Solid Insulating Materials - Dielectric and Resistive Properties (GB / T 31838.2-2019)", one side of the release film of the current-conducting adhesive-reducing tapes prepared in Examples 1-3 and Comparative Examples 1-4 was torn off, and the surface resistance of the corresponding adhesive surface was measured.
[0160] The test results are shown in Table 2.
[0161] V. Result Summary and Conclusion
[0162]
[0163] The current-conducting adhesive-reducing compositions and current-conducting adhesive-reducing tapes prepared in Examples 1-3 have excellent mechanical properties and adhesion ability compared with the current-conducting adhesive-reducing compositions and current-conducting adhesive-reducing tapes prepared in Comparative Examples 1-4. The adhesion can increase / decrease with the switching between non-current-conducting / current-conducting states, the current consumption is small, the cycle stability is good, and excellent adhesion can still be maintained at high temperature. The antistatic performance is excellent, which can reduce electrostatic adsorption and anti-pollution.
[0164] In the description of the specification, the description referring to terms such as "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.
[0165] The above content is only an example and explanation of the present invention. Those skilled in the art of this technology can make various modifications or supplements to the described specific embodiments or use similar methods to replace them. As long as they do not deviate from the invention or exceed the scope defined by the claims of the present invention, they should all fall within the protection scope of the present invention.
Claims
1. An electroconductive tackifier composition, characterized in that: It is made of the following raw materials counted by weight parts: 60 - 70 parts of polyurethane acrylate; 10 - 14 parts of PEDOT / PSS solution; 4 - 8 parts of nano core - shell material; 8 - 12 parts of dynamic cross - linker; 2.5 - 3.5 parts of TPU particles; 1 - 2 parts of hydrogenated rosin tackifying resin; 0.4 - 0.6 parts of poly(butylene adipate); 0.2 - 0.4 parts of antioxidant; 0.1 - 0.2 parts of zwitterion - polyethylene glycol copolymer; The dynamic cross - linker is ferrocene and β - cyclodextrin with a molar ratio of 1:(1 - 1.2); The preparation steps of the nano core - shell material are as follows: A1. Dispersed silver nanowires in PVP / ethanol solution for pretreatment, ultrasonic treatment for 30 min, centrifuged, then dispersed the pretreated silver nanowires in ethanol / water mixed solution, added 0.1 mol / L tetraethyl orthosilicate solution and 0.5 mol / L ammonia water, stirred at room temperature for 12 h, centrifuged at a speed of 12000 r / min for 10 min, and washed with ethanol 3 times to obtain core - shell material; A2. Dispersed the core - shell material in acetic acid buffer solution with pH of 5.5, ultrasonic treatment for 30 min, treated with 50 W oxygen plasma for 5 min, centrifuged, washed, and dried to obtain AgNWs@SiO2 material; A3. Added 3 - mercaptopropyltrimethoxysilane to ethanol aqueous solution, adjusted the pH value to 8 - 9, stirred to dissolve to obtain 3 - mercaptopropyltrimethoxysilane hydrolysis solution; dispersed AgNWs@SiO2 material in 3 - mercaptopropyltrimethoxysilane hydrolysis solution, stirred at 60 °C for 6 h under nitrogen atmosphere, centrifuged, washed, and dried to obtain nano core - shell material.
2. The electro-conductive tacky adhesive composition according to claim 1, wherein: In step A1, the mass fraction of PVP in the PVP / ethanol solution is 1%; the volume ratio of ethanol to water in the ethanol / water mixed solution is 4:1; the solvent of the tetraethyl orthosilicate solution is ethanol / water mixed solution.
3. The electro-conductive tacky adhesive composition according to claim 1, wherein: The solvent of the PEDOT / PSS solution is dimethyl sulfoxide.
4. The electroconductive tackifier composition according to claim 1, characterized in that: The hardness of TPU particles is 60A - 70A.
5. The electro-conductive tacky adhesive composition according to claim 1, wherein: The antioxidant is one or more of dibutylhydroxytoluene (BHT) and benzotriazole (BTA).
6. The electroconductive tacky adhesive composition according to claim 1, wherein: The zwitterion - polyethylene glycol copolymer is one or two of sulfobetaine - polyethylene glycol copolymer, carboxybetaine - polyethylene glycol copolymer, phosphatidylcholine - polyethylene glycol copolymer, phosphoric acid ester - based betaine - polyethylene glycol copolymer and aminobetaine - polyethylene glycol copolymer, and the molecular weight range of the polyethylene glycol segment is 2000 - 5000 Da.
7. A method for preparing an electroconductive tackifying adhesive composition according to any one of claims 1-6, characterized in that: It includes the following steps: S1. Added polyurethane acrylate and poly(butylene adipate) to a planetary stirring kettle at 25 - 30 °C, stirred at a speed of 200 - 300 r / min for 10 - 12 min; S2. Gradually added PEDOT / PSS solution, stirred at a speed of 500 - 600 r / min for 15 - 20 min; S3. Transferred the mixed material prepared in S2 to an ultrasonic disperser, slowly added nano core - shell material, 20 kHz, power 300 W, ultrasonic dispersion for 15 min, and maintained below 30 °C; S4. Transfer the mixed material obtained in S3 back to the planetary stirring kettle, successively add a dynamic crosslinking agent and 1 - 2 parts of hydrogenated rosin tackifying resin, and stir at a speed of 300 - 400 r / min for 18 - 20 min; S5. Add TPU particles and stir at a speed of 400 - 600 r / min for 20 - 25 min; S6. Add an antioxidant and an amphoteric ion - polyethylene glycol copolymer, and stir at a speed of 150 - 200 r / min for 10 - 12 min to obtain a mixed glue; S7. Vacuum - degas the mixed glue solution for 20 min to prepare an electrified tack - reducing glue composition.
8. An electrically conductive pressure-sensitive adhesive tape, comprising a release film layer I, an adhesive layer, and a release film layer II, characterized in that: The adhesive layer is obtained by curing the electrified tack - reducing glue composition according to any one of claims 1 - 6.
9. The preparation method of an electrically conductive adhesion-reducing tape according to claim 8, characterized in that: It includes the following steps: Use a doctor - blade coater to uniformly coat the electrified tack - reducing glue composition on the release film layer I, and cure it by UV for 60 - 90 s to obtain an adhesive layer, and then laminate the release film layer II on the other side of the adhesive layer to prepare an electrified tack - reducing tape.
Citation Information
Patent Citations
Silver nanowire coating liquid and preparation method thereof
CN109741853A
Reusable power-on viscosity-reducing adhesive tape with high shear strength and preparation method thereof
CN118389082A